Impact of spatial patterns on arthropod assemblages following natural dune stabilization under extreme arid conditions - Ittai Renan; Amnon Freidberg; Elli Groner; Pua Bar Kutiel (Global Journal of Ecology - Peertechz Publications, 2020)
Background: The cessation of anthropogenic activities in mobile sand dune ecosystems under xeric arid conditions has resulted in the gradual stabilization of dunes over the course of five decades.  Our objective was to analyze the spatial patterns of arthropod assemblages along a gradient of different stabilization levels, which represents the different stages of dune stabilization - from the shifting crest of the dune to the stabilized crusted interdune. The study was carried out at the sand dunes of the northwestern Negev in Israel. Data was collected using dry pitfall traps over two consecutive years during the spring along northern windward aspects. Four dunes were chosen, characterized by three significant landscape units: shifting crest, semi-stabilized slope and stabilized interdune. Results: We identified three significant assemblages of arthropods along the gradient. The shifting dune crests are populated by psammophilic species found almost exclusively in sandy habitats in Egypt and the western Negev in Israel. The crusted, stabilized inter-dunes are populated mainly by loess-dwelling species, which are common in most of the Negev loess plains and have a wide distribution range, and the semi-stabilized slopes host species of both extreme landscape units but is distinguished by four species that show significant affinity to it.  Conclusions: Our results demonstrate functional arthropod heterogeneity and emphasize the risk of regional species homogenization. Heterogeneity is a key property in maintaining sand dune biodiversity. Homogenization, as a result of sand stabilization, may lead to loss of psammophilic species.